A stylized satellite account for human capital - Gang Liu (Statistics Norway, Research Department, 2015)
This paper presents a satellite account in which investment in human capital is considered as a produced product/asset. It is not the education sector but the individual person taking education or training/courses that is the genuine producer of human capital. The former only provides education services that are used as one of the production inputs for the latter. Since another fundamental input is own labor services, human capital produced and embodied in the individual is regarded as being owned by the person in concern. It is demonstrated that the gross operating surplus generated from the production of human capital equals the differences between the estimates by the cost-based and the income-based approaches, which constitutes the first step towards making reconciliation between the estimates within one and the same framework. Finally, a numerical example based on supply and use tables shows the feasibility of implementing such a satellite account in practice.
Keywords: C82; E01; H52; I20; J24; 330; human capital; satellite account; output of education sector; supply and use tables